Effectiveness of Communication Skills Training on Increasing Self-Efficacy and Hopefulness of Veterans\' Wives; A Case Study of Ravansar City - Ch. Pardar; S. RezaKhani (Afarand Scholarly Publishing Institute, 2018)
Aims: Veteranschr('39') spouses are exposed to negative psychological consequences due to interaction with veterans. The purpose of this study was to investigate the effectiveness of communication skills training on increasing self-efficacy and hopefulness of veteranschr('39') wives. Materials & Methods: In this semi-experimental study, with pretest-posttest design with control group, 30 veteranschr('39') wives in Ravansar city, which had passed 10 years of their membership in martyr and Sacrificers Foundation by the end of 2014, were selected through targeted sampling. Then they were randomly assigned into two experimental and control groups (each group was 15). Research tools were General Self-efficacy Scale (GES-10) and Schneiderchr('39')s Hope Scale. Communication skills training was provided to the experimental group in 8 sessions of 90 minutes, once a week, but the control group did not receive any intervention. Data were analyzed by SPSS 20 using multivariate analysis of variance. Findings: By controlling the pre-test effect, there was a significant difference between experimental and control groups in post-test scores of self-efficacy, hopefulness, agency thinking and strategic thinking factors. Communication skills training resulted in 32% and 63% change in self-efficacy and hopefulness, as well as 59% and 49% in agency thinking and strategic thinking factors (p<0.001). Conclusion: Communication skills training is effective on increasing self-efficacy and hopefulness of veteranschr('39') wives.